Cytoplasmic Hydration Triggers a Transient Increase in Cytoplasmic Ca2+ Concentration in Nitella flexilis - Tazawa, Masashi; Shimada, Kiyo; Kikuyama, Munehiro (Oxford University Press, 1995)
Cells of Nitella flexilis were made inexcitable by treatment with 10 mM KCl for more than 24 h. A Ca2+-sensitive photoprotein aequorin was injected into the cytoplasm of such cells. For vacuolar per fusion, the central part of an aequorin-loaded cell was immersed in silicone oil, and both cell ends bathed in the perfusion medium were cut off. A large light emission from aequorin was observed when the vacuole was perfused with a hypotonic medium whose osmotic pressure was adjusted to half of the osmotic pressure of the cell sap. This shows that hydration of the cytoplasm triggers release of Ca2+ from internal stores, since influx of Ca2+ from silicone oil is excluded. Hydration of cells was induced in another way. Cells were first dehydrated by transferring them from 10 mM KCl solution to that with 250 mM sorbitol added. This procedure did not affect the cytoplasmic streaming. When cells were rehydrated by transferring them to 10 mM KCl solution, cytoplasmic streaming was either stopped or slowed down in a few seconds. A quick light emission from aequorin was observed in the rehydration, evidence that cytoplasmic streaming was inhibited by an increase in the cytoplasmic Ca2+ concentration. Both streaming cessation and aequorin light emission were observed even in KCl-treated cells which were further treated with 5 mM EGTA. Thus, the increase in Ca2+ is concluded to be caused by the release of Ca2+ from internal stores. These results support our previous hypothesis [Tazawa et al. (1994) Plant Cell Physiol . 35:63] that, in Nitella flexilis , the increase in the concentration of Ca2+ in the cytoplasm which occurs on the endoosmotic side of the cell during transcellular osmosis is caused by hydration of the cytoplasm.